(untitled) (Anclajes, 2018)
Focused on the narrative of two 21st century Argentine writers –Gerardo González y Facundo R. Soto– this article addresses the way their work reappropriates and resignifies some of the urban spaces most closely related to traditional patriarchy –the family house, the gym, and the soccer field. The article uses theoretical concepts such as Henri Lefebvre’s production of space and Michel Foucault’s heterotopy to show that González’ and Soto’s texts are mostly successful in challenging the paradigms of traditional urban planning and in queering said urban spaces.